Determinants of Local Government Performance with Organizational Commitment as A Moderating Variable - Hariyanto, Berliana Ika Putri; Wahyuni, Sri; Fitriati, Azmi; Santoso, Selamet Eko Budi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to determine the influence of regional financial supervision, accountability and transparency of regional financial management on regional government performance with organizational commitment as a moderating variable. Data collection uses primary data obtained from questionnaires through the use of a purposive sampling method. The population was 26 OPDs within the Pekalongan Regency Government, while the sample taken was 144 respondents. According to the hypothesis test carried out, regional financial supervision has a positive effect on regional government performance; The results of this research also show that accountability has a positive effect on local government performance; It was also found that transparency in regional financial management has a positive effect on regional government performance. Organizational commitment, which in this study is hypothesized as a moderating variable between the relationship between regional financial supervision, accountability and transparency of regional financial management and regional government performance, has not been proven, but organizational commitment has been proven to have a direct positive effect on regional performance. government performance.